Pengaruh Kepemimpinan Dan Pengembangan Karier Melalui Kepuasan Kerja Sebagai Variabel Intervening Terhadap Kinerja Karyawan Pada PT. SPBU Pisang Kota Padang - Arya Satria Yuda; Vicky Brama Kumbara; Putri Intan Permata Sari (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to examine the influence of leadership and career development on employee performance through job satisfaction as an intervening variable at PT. SPBU Pisang Kota Padang. Increasing business competition requires organizations to improve the quality of their human resources by implementing effective leadership, well-structured career development, and strategies to enhance job satisfaction in order to achieve better employee performance. This research employed a quantitative approach using a survey method. The population consisted of all employees of PT. SPBU Pisang Kota Padang, and a census sampling technique was applied, whereby all employees were included as research respondents. Data were collected through questionnaires developed based on the indicators of each research variable. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that leadership has a positive and significant effect on job satisfaction, career development has a positive and significant effect on job satisfaction, and job satisfaction has a positive and significant effect on employee performance. Furthermore, leadership and career development also have direct and indirect effects on employee performance through job satisfaction as an intervening variable. These findings suggest that improving leadership quality and implementing a well-planned career development system can enhance employees' job satisfaction, which in turn improves their performance. Therefore, organizations are encouraged to strengthen effective leadership practices and provide fair and sustainable career development opportunities to support the achievement of organizational goals.